Prevalence of Intestinal Protozoan Parasites in Adult Cancer Patients in Elazığ: A Cross-Sectional Study - Kaplan, Mustafa; Keleştemur, Neslihan; Mülayim, Sefa; Aksoy, Asude (My University, 2020)
Objective: Among cancer patients, immunosuppression due to the disease itself or the therapeuticagents used increases the risk of intestinal parasitic infections. The aim of the present study was todetermine the types of parasites, the incidence and risk factors that might affect the treatmentprocess and the life quality in cancer patients.Materials and Methods: This study was carried out in Firat University Hospital and 18 years oldand over oncology patients were followed up and treated. Stool specimens were taken 3 times (atleast once) on different days from patients and examined primarily by native and lugol methods.Subsequently, preparations prepared by applying the formol-ether concentration method wereexamined by specific staining methods.Results: Among 111 oncology patients, 43 (38.7%) were infected with one or more parasites. In 33(29.7%) patients, a parasite was detected, whereas 7 of them (6.3%) had two species, and 1 ofthem (0.9%) had three species of parasites. Blastocystis sp. was the most common parasiticspecies in 34 (30.6%) cases. Only commensal parasites were detected in 32 (28.8%) stoolspecimens and commensal and pathogenic parasites were detected in 11 (9.9%) stool specimens.There was no significant difference in the distribution of parasitic infections according todemographic characteristics, disease history, personal hygiene habits, clinical status andcomplaints of the patients.Conclusion: The prevalence of intestinal protozoa in our study group is higher than the prevalencedetected in the normal population in our region. We think that this area needs more research,which will help clinicians and create new approaches for patients' treatment and follow-up.
Keywords: Biyoloji; Genel ve Dahili Tıp; Mikrobiyoloji; Parazitoloji; Onkoloji